THE DIALECTIC OF USURY AND LIQUIDITY NEEDS: AN ISLAMIC LEGAL REVIEW OF SHARIA BANK FUND PLACEMENTS IN CONVENTIONAL BANKS IN INDONESIA - Iib Hibaturohman; Atang Abdul Hakim; Dena Ayu; Muhammad Tegar Syaekhudin (al-Mawarid Jurnal Syariah dan Hukum (JSYH), 2026)
Purpose - This study departs from the normative problem of placing Islamic bank funds in conventional banks, which continues amid limited Islamic liquidity instruments, causing tension between the qaṭ‘ī prohibition of usury and the need for systemic liquidity in the dual banking system. This study aims to determine the extent to which the placement of Islamic bank funds in conventional banks is permissible under Islamic law and the limits of permissibility that can be maintained without reducing the principle of non-usury (ribā). Method - This study uses a normative qualitative method based on fiqh and uṣūl al-fiqh analysis oriented towards maqāṣid al-sharī‘ah, with analysis techniques in the form of content analysis and comparative legal analysis of the views of contemporary scholars, DSN-MUI fatwas, and Indonesian and Financial Services Authority regulations. Finding - The permissibility of fund placement can only be positioned as a temporary rukhsah based on ḥājah that is close to systemic emergency, with operational indicators in the form of the absence of adequate sharia liquidity instruments, time and nominal restrictions in proportion, non-interest schemes, and strict and continuous sharia supervision. The legitimacy of this permissibility is casuistic and contextual and cannot be normalized as a permanent practice in Shariah banking liquidity management. This study affirms a moderate-critical normative approach that acknowledges the regulatory reality in the dual banking system while still placing the non-usury principle and the principle of Sharia prudence as the main ethical-juridical boundaries in preventing the shift of Sharia principles in contemporary financial practices. Contribution - This research contributes to the conceptual reformulation of temporary rukhsah as an operational legal category in contemporary fiqh al-mu‘āmalah and the strengthening of sharia liquidity instruments. Limitations - The limitations of this research lie in its predominantly normative-conceptual basis of analysis, which is not yet supported by comparative empirical data across Islamic banking institutions.